The impact of tillage practices on daytime CO2 fluxes, evapotranspiration (ET), and water-use efficiency in peanut - Bogati, Sujata; Leclerc, Monique Y.; Zhang, Gengsheng; Kaur Brar, Sukhvir; Tubbs, Ronald Scott; Monfort, Walter Scott; Hawkins, Gary Lawrence (Frontiers in Agronomy, 2023)
Peanut (Arachis hypogaea L.) growers use different tillage systems in the southeast USA the impact of which needs to be assessed with regards to evapotranspiration, carbon uptake and water-use efficiency (WUE). The eddy-covariance method was used to measure of these fluxes in peanut in two common tillage systems (strip tillage versus conventional tillage) over the course of three consecutive growing seasons (2019)(2020)(2021). Results suggest that during the dry year of 2019 with rainfall of only 30 cm, strip tillage peanut had a significantly higher day time ecosystem water-use efficiency, 105%, 51%, and 32% higher than the conventional tillage in early, mid, and late growth stages, respectively. In 2020 with mean rainfall the overall difference in average WUE was nonsignificant between tillage systems. Heavy rainfall of 112 cm in 2021 led to waterlogged conditions in the conventional tillage field due to poorer infiltration. This likely reduced the CO2 uptake. Water logging did not occur in the strip tillage field due to improved infiltration. As a result, in 2021, 18%, 33%, and 48% greater ecosystem WUE in strip tillage during early, mid, and later stages were found. Thus, this study suggests that strip tillage fields can achieve higher net CO2 uptake and WUE in Georgia during dry or very wet years. However, no difference in WUE was found between different tillage systems in a typical year. The present study has implications for regions characterized with long growing seasons and low rainfall.